Investigation of polymorphism and expression of the tyrosinase (TYR) gene as a gene controlling coat color in Bali cattle - Kholijah, K.; Darwati, S.; Ulum, M. F.; Londra, I. M.; Noor, R. R.; Jakaria, J. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
Cattle coat color is governed by numerous genes, notably the tyrosinase gene (TYR). This study analyzed coat color anomalies like albinism and white spotting in Bali cattle. It aims to discern the TYR gene's diversity, expression patterns, and correlation with coat color abnormalities. The research encompassed 189 cattle, including those with standard coat color (n=53), white-spotted (n=11), and albino (n=17) Bali cattle, as well as Simmental (n=37), Limousin (n=14), Madura (n=21), and Peran-akan Ongole (PO) cattle (n=36). Total DNA was extracted and the TYR gene in exon 1 was amplified using forward and reverse primers with a target amplicon length of 994 bp. Direct sequencing unveiled TYR gene diversity, analyzed using BioEdit and MEGA6 software to identify SNPs. PCR-RFLP was used for SNP genotyping, while qPCR analyzed TYR gene expression. Two mutations (SNP g. 939A>G and SNP g. 887C>T) were discovered in Bali cattle TYR exon 1. SNP g. 939A>G exhibited polymorphism, with the highest GG genotype frequency in standard Bali cattle, indicating a high G allele frequency. Conversely, Madura, Simmental, Limousin, and PO cattle had the lowest allele fre-quency. Chi-square (χ² test) results showed non-significance across all cattle types. TYR gene expres-sion differed significantly between standard Bali cattle and albinos (p<0.05).